(untitled) (Journal of Applied Oral Science, 2022)
While the combined effect of microwave irradiation with cleansing solutions on denture base materials has been investigated, the effects of only using microwave irradiation and, more importantly, in a long-term basis, was not studied yet. Objective: The purpose of this study was to evaluate the effect of a long-term repeated microwaving on the dimensional, color and translucency stability of acrylic and polyamide denture base materials. Material and Methods: Thirty two specimens (32 mm x 10 mm x 2.5 mm) from polyamide (Valplast) and PMMA (Vertex Rapid Simplified) denture base materials were made. Eight specimens from each material were immersed in distilled water (control) and 8 were subjected to microwave exposure at 450 W for 3 minutes for a period simulating 224 days of daily disinfection. Linear dimension, color change (ΔE*) and translucency parameter (TP) were measured at baseline and after certain intervals up to 224 cycles of immersion, using a digital calliper and a portable colorimeter. The results were analysed using two-way repeated measures ANOVA to estimate possible differences among predetermined cycles and material type. Regression analysis was also performed to estimate the trend of changes with time. Statistical evaluations performed at a significance level of 5%. Results: Data analysis showed significant changes in length at baseline with an increasing number of cycles (p<0.05) and a significant interaction of cycle-material (p<0.001). The ΔΕ* parameter was significantly higher with a higher number of cycles (p<0.001), but it did not vary between materials (p>0.05). TP decreased similarly in both materials following microwave action but in a significantly higher level for Valplast (p<0.001). Conclusions: The results indicated that long-term repeated microwaving affects linear dimensional, color and translucency changes of both materials. Differences between PMMA and polyamide material were noted only in dimension and translucency changes.